Persepsi Stres dan Fungsi Imun: Tinjauan Literatur dalam Perspektif Psikoneuroimunologi - Ludfiah Azahra; Tasya Cahya Salsabila; Faula Aldini Putri; Shalma Fadilla; Wirza Feny Rahayu (CV. ITTC INDONESIA, 2026)
This scoping review aims to synthesize empirical evidence on the association between perceived stress and immune function as examined within the framework of psychoneuroimmunology. Using PRISMA-ScR guidelines, four empirical studies published between 2016 and 2025 were selected from Semantic Scholar and PubMed. The review integrates evidence across various populations, including pregnant women, cancer patients, individuals with HPV infection, and healthy adults. Findings consistently show that high perceived stress is linked to measurable physiological changes, such as decreased immune gene expression, reduced T-cell and NK-cell activity, heightened systemic inflammation, microbiome imbalance, and accelerated immunosenescence. These results underscore that subjective psychological appraisal plays a central role in shaping biological vulnerability, demonstrating the interconnectedness of mental and physical health. The study highlights the importance of psychological interventions, such as cognitive restructuring, coping enhancement, and stressmanagement training to protect immune health. Future research should incorporate culturally relevant psychological factors and immune biomarkers to deepen understanding within the field of health psychology.